Synthesis and Characterisation of Bridged Titanocene Oxido Complexes and Their Reactions with Water1. Issue 25 (30th July 2014) - Godemann, Christian; Barsch, Enrico; Spannenberg, Anke; Ludwig, Ralf; Beweries, Torsten
Abstract: The synthesis of two pyridine‐stabilised ansa ‐titanocene oxido complexes is described. Oxidation of the titanocene sources Cp b 2 Ti(η 2 ‐Me3 SiC2 SiMe3 ) (Cp b 2 = bridged η 5 ‐cyclopentadienyl, 1a and1b ) with nitrous oxide yields corresponding oxido compounds2a and2b, respectively, in high yields. These can be hydrolysed to give dihydroxido complexes3a and3b, respectively, without the formation of by‐products. The hydrolysis reaction was monitored by means of in situ IR spectroscopy. Hitherto unknown complexes2a and2b were fully characterised, and their molecular structures are reported in this paper. Abstract : Oxidation of titanocene alkyne complexes with nitrous oxide in the presence of pyridine gives the corresponding ligand‐stabilised oxido complexes, which can be hydrolysed to yield dihydroxido compounds quantitatively in very short reaction times, as evidenced by stopped‐flow IR spectroscopy.